The Effect of Chanting Om Mantra on Health: A Review - Vivek; Minhas, Prashant; Dikshika (International Research Journal of Ayurveda & Yoga, 2023)
Today we are heading toward materialistic progress at the cost of our health, physical as well as mental. In this blind pursuit, instead of peace we end up in stressed life. Unfortunately, neither we understand that we are under stress nor get any training of stress management while we study or work. In this modern world there are many diseases, disorders and complications but some complications are commonest and almost each and every human being in this modern world has it, it is stress, depression and there are many medications which claims to get relief from it but only for some duration and that too has some of its side effects but, “OM” (AUM) chanting is such a traditional practice which has beneficial effects not just in relieving stress and depression but can also give relief from many mental and physical complications and has of course no side effects and once if learnt properly do not need any guidance. Regularly chanting of OM) can be used in daily lifestyle can be more beneficial. Present review compiles the studies which evaluated that chanting OM mantra has the positive effect on the human health.